E EVALUASI PROGRAM SEKOLAH SEHAT DALAM MENGEMBANGKAN PERILAKU SEHAT PADA SMA DI INDRALAYA SELATAN - EVALUASI, Fithriani; Putra, Alhadi Yan; Rosani, Meillia (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
This study evaluates the Healthy Schools Program at senior high schools in South Indralaya and its impact on students' healthy behavior development. The results showed that high schools in South Indralaya have successfully implemented the Healthy Schools Program, which has a positive impact on the development of students' healthy behaviors. The program includes physical education, nutrition, environmental sanitation, and school health services. Collaboration between BK teachers, UKS, sports teachers, healthy canteen officers, and community health centers increased students' awareness of the importance of balanced nutrition and healthy lifestyles. Students began to implement healthy eating habits, maintain personal hygiene, exercise regularly and choose healthy foods. Increased physical activity through school sports contributes to fitness and a reduced risk of obesity. Hygiene initiatives, such as waste management, also encourage cleanliness practices at home and school. In addition, mental health awareness increased and students were more proactive in seeking emotional support. Environmental education programs foster students' concern for the environment through activities such as tree planting.